O Impacto da Internacionalização com Foco na Inovação Tecnológica sobre as Exportações das Firmas Brasileiras - Glauco Arbix; Mario Sergio Salerno; João Alberto De Negri (Universidade do Estado do Rio de Janeiro, 2005)
Based on an unprecedented link between the principal official databases on Brazilian industry - the Industrial Survey on Technological Innovation (Pintec) and the Annual Industrial Survey (PIA) of the National Census Bureau (IBGE); the foreign trade database of the Ministry of Development, Industry and Foreign Trade - Mdic, and the Annual Report on Social Data of the Ministry of Labor and Employment (RAIS/MTE) - this study showed that the companies that use their offices abroad as a source of information for technological innovation show superior performance to the rest: they are larger, import and export more, pay higher salaries, employ workers with more education, and spend relatively more on training activities. The probability of a company exporting increases by 16% when it invests in technological innovation. These results indicate the need to reflect on public policies to support innovation and internationalization in Brazilian companies.